Unresponsive feeding practices in overweight and obese suburban preschool-aged children: A qualitative case study - Astuti, Astuti; Winahyu, Karina Megasari; Perdani, Zulia Putri; Mulmuang, Susheewa Wichaikul; Kartini, Kartini (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Irresponsible feeding behavior is the cause of being overweight in early childhood. Purpose: This study aimed to investigate the dietary habits of preschool-aged children residing in a suburban region of Indonesia characterized by a significant prevalence of obesity among children aged five and below. Methods: This study was a case study design conducted in South Tangerang, Banten Province, Indonesia, involving six moms who had toddlers with overweight to obese nutritional status. The number of six participants was decided after the saturation coding of the fifth participant, and then one more participant was interviewed to ensure that the data was genuinely saturated. The mothers were selected to participate in the study and were interviewed in depth. The researcher also observed the participants' eating behavior. The analytical framework was used in this research, and then the interview transcripts were analyzed using thematic analysis. Results: The four themes found were 1) The inability to respond to internal cues of satiety, 2) Distraction at mealtimes, 3) Unhealthy food in emotional eating, and 4) Mothers practice persuasive feeding. Conclusions: The children show unresponsive feeding behavior, which notably contributes to the prevalence of overnutrition during early childhood. Community health professionals should strengthen their efforts to improve feeding behaviors among mothers to address the nutritional status of preschool-aged children.